Delays in switching patients onto second-line antiretroviral treatment at a public hospital in eThekwini, KwaZulu-Natal - Denver Narainsamy; Saajida Mahomed (AOSIS, 2017)
Background: South Africa has one of the largest antiretroviral treatment (ART) programmes globally. In addition to increasing access to ART, it is important that the health system also focuses on the appropriate management of patients who fail first-line ART. Delays in switching patients onto second-line ART can adversely affect patient outcomes. Aim: To identify the patient-related and programmatic factors that delay switching patients onto second-line ART, and to assess whether these delays contribute to subsequent virological failure. Methods: Clinical records of adult patients switched onto second-line ART between 2011 and 2014 at a public antiretroviral clinic were used to collect demographic, clinical, laboratory and programmatic data (availability of viral load results, inadequate patient follow-up, insufficient notes for effective follow-up). Data were analysed using univariate and multivariate logistic regression. Results: The median duration from the date of first and confirmatory documented high viral load (VL > 1000 copies/mL) to being switched to second-line ART was 13.2 months [interquartile range (IQR) 1.1-52.7 months] and 6.4 months (IQR 0-43.3 months), respectively. Inadequate prescriber notes for appropriate follow-up (p = 0.01) and unavailability of patients' viral load results (p = 0.02) were significantly associated with delays in switching to second-line ART. There was no significant association between the time taken to switch to second-line ART and subsequent virological failure. Conclusion: We observed lengthy delays in switching patients to second-line ART. Modifiable programmatic factors were found to be significantly associated with delays in switching to second-line ART.